Boom! [compact disc, unabridged] - Haddon, Mark, 1962- (Random House/Listening Library, 2010)
When Jim and Charlie overhear two of their teachers talking in a secret language and the two friends set out to solve the mystery, they do not expect the dire consequences of their actions.